2003
DOI: 10.1103/physrevlett.91.262501
|View full text |Cite
|
Sign up to set email alerts
|

Spin Symmetry in the Antinucleon Spectrum

Abstract: We discuss spin and pseudo-spin symmetry in the spectrum of single nucleons and single antinucleons in a nucleus. As an example we use relativistic mean field theory to investigate single anti-nucleon spectra. We find a very well developed spin symmetry in single anti-neutron and single anti-proton spectra. The dominant components of the wave functions of the spin doublet are almost identical. This spin symmetry in anti-particle spectra and the pseudo-spin symmetry in particle spectra have the same origin. How… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
246
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(255 citation statements)
references
References 13 publications
7
246
0
2
Order By: Relevance
“…The structure (44) also holds for antiparticles in Woods-Saxon scalar and vector mean-field potentials, as shown in Refs. [3,6]. This may be because these potentials are finite at r = 0, as are the nuclear mean-field scalar and vector potentials, and thus the behavior of the respective radial functions at the origin is different from the present case of Coulomb potentials.…”
Section: A Node Structure Of the Solutionsmentioning
confidence: 79%
See 1 more Smart Citation
“…The structure (44) also holds for antiparticles in Woods-Saxon scalar and vector mean-field potentials, as shown in Refs. [3,6]. This may be because these potentials are finite at r = 0, as are the nuclear mean-field scalar and vector potentials, and thus the behavior of the respective radial functions at the origin is different from the present case of Coulomb potentials.…”
Section: A Node Structure Of the Solutionsmentioning
confidence: 79%
“…However, for bound systems whose potentials go to zero at infinity, pseudospin symmetry cannot be realized, because = S + V (which must go to zero in the limit of exact pseudospin symmetry) is also the binding potential. Recently there has been a considerable interest in studying antifermions in the context of spin and pseudospin symmetries, for antinucleon systems [3][4][5][6] and antihyperons systems [7]. In this case, one cannot have exact spin symmetry (i.e., V = S) since now − = −(V − S) acts as binding potential.…”
Section: Introductionmentioning
confidence: 99%
“…It includes naturally the nucleonic spin degree of freedom and automatically results in the nuclear spin-orbit potential with the empirical strength in a covariant way. It can reproduce well the isotopic shifts in the Pb region [35], and give naturally the origin of the pseudospin symmetry [36] and the spin symmetry in the anti-nucleon spectrum [37,38]. Furthermore, it can include the nuclear magnetism [39], that is, a consistent description of currents and time-odd fields, which plays an important role in nuclear magnetic moments [40][41][42][43][44] and nuclear rotations [33,[45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, it has received wide attention due to its success in describing many nuclear phenomena for the stable nuclei [2,3] as well as nuclei even far from stability [4,5]. It has been shown that the relativistic Brueckner theory can reproduce better the nuclear saturation properties (the Coester line) in nuclear matter [6], present a new explanation for the identical bands in superdeformed nuclei [7] and the neutron halo [8], predict a new phenomenon -giant neutron halos in heavy nuclei close to the neutron drip line [9], give naturally the spin-orbit potential, the origin of the pseudospin symmetry [10,11] as a relativistic symmetry [12,13,14] and spin symmetry in the anti-nucleon spectrum [15], and present good description for the magnetic rotation [16] and the collective multipole excitations [17], etc.…”
Section: Introductionmentioning
confidence: 99%